West's Federal Taxation: Corporations, Partnerships, Estates and Trusts. - Goodman, Bernard B. (The Accounting Review, 1981)
Reviews the book "West's Federal Taxation: Corporations, Partnerships, Estates and Trusts," edited by William H. Hoffman.